PENGEMBANGAN LEMBAR KERA PESERTA DIDIK ELEKTRONIK BERBASIS MULTIPLE INTELLIGENCES MATERI SISTEM PERTAHANAN TUBUH - Arini Arun Dani; Evi Suryawati; Arnentis Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Each student has different abilities and intelligence. So, it is important for teachers to plan learning by implementing appropriate learning strategies, one of which is the Multiple Intelligences learning strategy. The implementation of this strategy must be supported by the use of appropriate teaching materials, one of which is LKPD based on Multiple Intelligences. This study aims to develop quality LKPD based on Multiple Intelligences on Immunity System material. This research was conducted at the Biology Education FKIP UNRI, SMAN Plus Provinsi Riau, and SMAN 15 Pekanbaru in August 2020 – April 2021. It used a Research and Development (R&D) approach with ADDIE model. The instruments used are validation and response questionnaires. The results of achieving an average value of 3.66 categories are very valid. The results of the limited trial phase I obtained an average value of 3.40 in the very good category. The results of the limited trial phase II obtained an average value of 3.26 in the very good category. The results showed that the Electronic LKPD based on Multiple Intelligences on immunity system materials had been developed and of good quality and suitable to be used as a learning resource.Key Words: Student Worksheet, Electronic, Immunity System